Effects of Polymorphisms in NR1H4, NR1I2, SLCO1B1, and ABCG2 on the Pharmacokinetics of Rosuvastatin in Healthy Chinese Volunteers. Issue 5 (November 2016) - Liu, Mei; Wu, Xiu-Jun; Zhao, Gui-Lian; Zhang, Ti; Xu, Shan-Sen; Sun, Ya-Xin; Qiu, Feng; Zhao, Li-Mei
Abstract : Abstract: The nuclear receptors (NR)—farnesoid X receptor (FXR, NR1H4 ) and pregnane X receptor (PXR, NR1I2 )—have important effects on the expression of genes related to the pharmacokinetics (PKs) of rosuvastatin. This study was designed to investigate whether the genetic variants in drug disposition genes ( SLCO1B1 and ABCG2 ) combined with their upstream regulators ( NR1H4 and NR1I2 ) would affect the PKs of rosuvastatin in a Chinese population. Sixty-one healthy male volunteers were enrolled and the plasma concentrations of rosuvastatin were measured using the liquid chromatographic—tandem mass spectrometry/MS method. All subjects were analyzed and grouped according to the genotypes of NR1H4, NR1I2, SLCO1B1, and ABCG2 . The exposure of rosuvastatin was higher in subjects carrying the SLCO1B1 521C or ABCG2 421A allele compared with noncarriers. No association was observed of single-nucleotide polymorphisms in NR1H4 or NR1I2 genes with the PKs of rosuvastatin. After adjusting for the 421C>A and 521T>C variants, the Cmax in subjects with NR1I2 63396TT wild type were about 2-fold of those of NR1I2 mutant type (63396CC and CT) (10.7 vs. 20.4 ng/mL, P = 0.023), whereas no significant differences were observed for other parameters. Polymorphisms investigated in the genes of NR1H4 and NR1I2 seemed to play no significant role in the disposition of rosuvastatin.